Improvement of Physicochemical Properties of RBD Palm Olein Blended with Soybean Oil for Deep-Fat Frying - Liu, Jia Long (1999)
The quality changes of refined, bleached and deodorised palm olein (RBDPOo), soybean oil (SBO) and their blends during intermittent deep-fat frying at 180±5°C for 5h per day for 5 consecutive days were studied. The shelf-life of potato chips used for frying was also investigated. The results showed that the physicochemical properties of SBO were improved by blending with RBDPOo in terms of resistance to oxidation, iodine value (IV), anisidine value (AnV), foaming tendency, % polar component and polymers content. However, SBO also contributed to RBDPOo with respect to colour, viscosity, free fatty acids (FF A) content and smoke point. Sensory evaluation showed that potato chips fried in both of RBDPOo and SBO were equally preferred by the panellists. Shelf-life stability of the fried potato chips indicated that chips fried in RBDPOo were better than that fried in SBO. The blends of RBDPOo : SBO were improved with increasing proportion of RBDPOo. The observation showed that there were minimal effects on the rate of development of rancidity in the fried product beyond the fourth day of frying in all blends. The changes of RBDPOo with added TBHQ and (X-tocopherol during deep-fat frying were also studied. Addition of antioxidants resulted in improved oxidative stability. TBHQ was more effective in reducing the level of FF A, polar component and polymers and decreased the rates of change in IV and the ratio of C18:2/C16:0. (Xtocopherol was more effective in reducing AnV and totox values. However, adding antioxidants caused darkening of oils and increased the formation of foam during deep fat frying. Differential scanning calorimetry (DSC) was also used to monitor IV, peroxide value (PV), AV and FFA of frying oils. The heating thermogram was from -50 to 80°C at a heating rate of 5°C/min, whereas, the cooling thermogram was at the same rate from 80 to -50°C. Stepwise multiple linear regression (SMLR) analysis showed that peak characteristics, namely peak temperature, enthalpy and peak height of heating and cooling thermo grams can predict the parameters such as IV, PV, AV and FFA of the samples with the coefficient of determination (R2) at least 0.9300. Thus, this study showed that DSC method can monitor these quality parameters of fried oils to replace wet chemical methods which involve a large number of toxic and environmental unfriendly solvents and reducing the labour cost as well.